(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Monitoring was done both inside and outside the classrooms. Measurements were taken during complete college hours (5-6 hrs), along with each 30 minutes before (in morning, when college starts) and after the college (in afternoon, when college gets over). This feature was practice in order to evaluate PM levels, when classrooms were occupied and when unoccupied, as the sampling duration was restricted for lecturing hours only. Intermediate to B. A., B.Sc. classrooms were chosen for monitoring at college. Due to unavailability of students during summer vacations (in June) and no allowance for sampling during examinations (in March), the respective two months were not included in the sampling schedule, along with weekends and government holidays.